Interiority and The Conditions of Interior - Pimlott, Mark (Interiority, 2018)
Interiority pertains to the individual’s inner life, rich and set in opposition to the pressures of the world. This interiority has been allied with notions of the exclusive space or refuge of the interior. As a realm of privacy and subjectivity, of projections and receptions, the interior has come to be considered as a realm that, although profoundly affected by infiltrations of the world without, is ‘responsive’ to the individual at its centre. As such, it is a realm of illusions. However, there is another order of interior, a condition of interior, wherein spaces, settlements and territories are ideological realms of constructed narratives and imagery within which the individual subject is given illusory impressions of freedom. Interiority’s turn toward the imagination suggests that freedoms can be found despite these determinations. Public interiors have the obligation to realise this, and exemplars have offered places for gathering and interaction, promoted freedoms of movement, association and action, and advocated consciousness of the self and others.